Legal Protection for Creditors Over Mortgage Rights Cancelled by Court Decisions (Court Decision Study) No. 136/Pdt.G/2019 Pn Ckr) - Triwibowo, Bagus; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. The Mortgage Law states that land rights that can be used as collateral include Ownership Rights, Cultivation Rights, Building Rights, and Usage Rights over State land, as long as these rights must be registered in accordance with applicable provisions and have a nature that can be transferred to another party. Mortgage rights provide legal certainty for the parties in a credit agreement, especially through the principle of specialization which gives special rights to the mortgage holder to be prioritized in fulfilling performance if the debtor defaults or fails to fulfill its obligations. This research falls into the category of normative legal research, conducted by analyzing library materials or secondary data. This research uses a statute approach, which emphasizes legal material as the primary basis for conducting the research. The research results show that Decision No. 136/Pdt.G/2019/PN Cikarang annulled the Mortgage Right and created legal uncertainty, even though the UUHT should have provided certainty for creditors. This annulment emphasizes the importance of material aspects in the validity of collateral. Bank BTN has carried out credit procedures and the imposition of Mortgage Rights legally, but the debtor's actions (YPR) have given rise to a dispute. Although the debtor's principal obligations remain, the collateral loses legal force. Protection for creditors is repressive through civil lawsuits (Article 1365 of the Civil Code), internal bank mechanisms (PBI No. 7/2/PBI/2005), criminal channels, and the right to demand compensation or alternative collateral. Keywords: Certainty; Court Decisions; Mortgage Rights.